Utopia for realists and how we can get there - Bregman, Rutger (London Bloomsbury, 2017)
In Utopia for Realists, Rutger Bregman shows that we can construct a society with visionary ideas that are, in fact, wholly implementable. Every milestone of civilisation ? from the end of slavery to the beginning of democracy ? was once considered a utopian fantasy. New utopian ideas such as universal basic income and a fifteen-hour work week can become reality in our lifetime.
Includes bibliographical references
Keywords: General & world history; Utopias; Social prediction; Guaranteed annual income; Wealth; Income; Workweek; Boundaries; Popular economics; Philosophy -- Political; Social & political philosophy; Electronic books